A clinical study of inferior mesenteric artery typing in laparoscopic radical resections with left colonic artery preservation of rectal cancer - Jinghao Chen; Meirong Wang; Yuhao Chen; Suying Chen; Jing Xiao; Xiaole Fan; Jushun Yang; Bosheng He (World Journal of Surgical Oncology, 2022)
Highlights 1. DECT three-dimensional reconstruction can accurately evaluate the classification of IMA before operation. 2. The short-term outcome of Dixon surgery with LCA preservation is affected by the type of IMA presented.